2008
DOI: 10.1124/jpet.108.146589
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Role for Sodium-Dependent Glucose Transport across the Blood-Brain Barrier during Oxygen Glucose Deprivation

Abstract: In the current study, we determined the functional significance of sodium-dependent/-independent glucose transporters at the neurovasculature during oxygen glucose deprivation (OGD). Confluent brain endothelial cells cocultured with astrocytes were exposed to varying degrees of in vitro stroke conditions. Glucose transporter (GLUT) 1 and sodium glucose cotransporter (SGLT) activity were investigated by luminal membrane uptake and transport studies using [3 H]D-glucose and also by [ 14 C]␣-methyl D-glucopyranos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 39 publications
5
86
0
Order By: Relevance
“…Since strongest effects on glut1 regulation were found after OGD, further investigations were done under OGD conditions. Recently, presence and functional relevance of a second glucose transporter at the BBB, called sglt1, was reported [4,15,23]. Results shown in figure 2 revealed that mRNA of sglt1 was significantly downregulated during six hours of OGD (0.57-fold, p<0.001) compared to according normoxia samples.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…Since strongest effects on glut1 regulation were found after OGD, further investigations were done under OGD conditions. Recently, presence and functional relevance of a second glucose transporter at the BBB, called sglt1, was reported [4,15,23]. Results shown in figure 2 revealed that mRNA of sglt1 was significantly downregulated during six hours of OGD (0.57-fold, p<0.001) compared to according normoxia samples.…”
Section: Resultsmentioning
confidence: 67%
“…Furthermore, functionality of sglts in BBB models was shown in vitro and an important role for sglts in vivo in edema formation during stroke was suggested [15,23]. However, sglt functionality at the BBB under physiological conditions is under doubt [25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…accounts for the majority of glucose entry into CNS tissue through brain vascular endothelial cells, although there is evidence that SGLTs can also contribute to this process (87). The main astrocytic glucose transporter is GLUT1, while neurons, by contrast, express mainly GLUT3 which has a higher transport activity than GLUT1 (88).…”
Section: Slc2a Glucose Transportersmentioning
confidence: 99%